2011
DOI: 10.1089/vbz.2010.0117
|View full text |Cite
|
Sign up to set email alerts
|

Urban Focus ofRickettsia typhiandRickettsia felisin Los Angeles, California

Abstract: Classic murine typhus, caused by Rickettsia typhi, is endemic in the continental United States in areas of Texas and southern California. We conducted an environmental investigation in an urban area of Los Angeles identified as the probable exposure site for a case of murine typhus. Four Rattus norvegicus heavily infested with Xenopsylla cheopis (average 32.5 fleas per animal, range 20-42) were trapped, and fleas, blood, and tissues were collected. DNAs from all specimens were tested for R. typhi and Rickettsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…That being said, more than one Bartonella sp. was identified in that study (Gundi et al 2012), and R. typhi (Abramowicz et al 2011) has been found in rats from Los Angeles. Genetic characterization of global rat population structures may help to elucidate the distribution of RAZ among different cities.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…That being said, more than one Bartonella sp. was identified in that study (Gundi et al 2012), and R. typhi (Abramowicz et al 2011) has been found in rats from Los Angeles. Genetic characterization of global rat population structures may help to elucidate the distribution of RAZ among different cities.…”
Section: Discussionmentioning
confidence: 75%
“…Although spleen has been successfully used for detecting R. typhi infection in rats (Abramowicz et al 2011), the period of active rickettsemia detectable by PCR can be transient (i.e., < 1 month) (Azad 1990), and the bacterium can be maintained in fleas (the vectors for transmission) (Azad 1990, Azad andBeard 1998). For these reasons, negative PCR results alone cannot completely rule out the presence of circulating R. typhi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a larger sample of X. cheopis and other flea species, it would be of interest to test for the presence of coinfection with R. felis and R. typhi in the same positive fleas, because it was previously reported in experimental works 42 and under natural conditions. 22,43,44 The analysis of the sequence electropherograms showed lack of ambiguity in the nucleotide assignments for all samples included. Because the PCR products were derived from pools in which several members could be positive, the clean sequence reads suggest that the amplified fragments were highly conserved and/or that only one flea in each pool was positive for a single Rickettsia.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of R. typhi in fleas and rodents DRC is one of the highest from the world. In the last years, R. typhi was identified in 10.8% of X. cheopis pools (4 of 16) in Indonesia, 33 in tissues from three rats and in 10% of fleas from each animal in California, 34 in 4% X. cheopis and 6.6% in Leptopsylla segnis in Cyprus, 35 and in 3.2% flea pools in Korea. 36 The flea remains infected with R. typhi for life with good fitness and the horizontal and vertical transmission increase the infected populations in this endemic area.…”
Section: Discussionmentioning
confidence: 99%